Acupuncture analgesia for temporal summation of experimental pain: a randomised controlled study - Zheng, Zhen; Feng, Sam Jian Qiang; Costa, Cliff da; Li, Chun Guang; Lu, David; Xue, Charlie Changli (European journal of pain, 2010)
Temporal summation of pain, a phenomenon of the central nervous system (CNS), represents enhanced painful sensation or reduced pain threshold upon repeated stimulation. This pain model has been used to evaluate the analgesic effect of various medications on the CNS. The present study aimed to evaluate the effects and characteristics of analgesia induced by electroacupuncture (EA), manual acupuncture (MA) and non-invasive sham-acupuncture (SA) in healthy humans on temporal summation of pain. Thirsty-six pain-free volunteers were randomised into one of the three groups EA (2/100 Hz), MA or SA. Acupuncture intervention was on ST36 and ST40 on the dominant leg delivered by an acupuncturist blinded to the outcome assessment. Both subjects and the evaluator were blinded to the treatment allocation. Pain thresholds to a single pulse (single pain threshold, SPT) and repeated pulses electrical stimulation (temporal summation thresholds, TST) were measured before, 30 min after and 24h after each treatment. The baseline values of three groups were comparable. Compared to SA, EA significantly increased both SPT and TST immediately after the treatment on the treatment leg as well as 24h after on both the treatment and non-treatment legs (ANOVA, p<0.05). MA also increased SPT and TST, but the changes were not significantly different from those induced by SA. EA induces bilateral, segmentally distributed and prolong analgesia on both SPT and TST, indicating a non-centrally specific effect. This effect needs to be verified with heat or mechanical model and in pain patients.